2015
DOI: 10.1007/s10964-015-0402-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Asynchronous Pubertal Development on Depressive Symptoms in Adolescence and Emerging Adulthood Among Females

Abstract: Puberty is accompanied by numerous psychological and interpersonal challenges, including a dramatic rise in the prevalence of depression among girls. Pubertal timing has been identified as a potent predictor of depressive symptoms among females, but less is known about other features of puberty. The present study sought to address this gap in the literature by examining the effect of pubertal synchrony, the degree to which morphological indicators of puberty develop concurrently, on depressive symptoms in adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
(93 reference statements)
1
13
0
Order By: Relevance
“…Pubertal asynchrony puts girls at risk of peer victimization above and beyond pubertal status and other covariates. The finding is consistent with prior work showing the positive link between pubertal asynchrony and maladjustment, such as depression, in girls (Stumper et al, 2020;Thompson et al, 2016). In explaining the association between pubertal asynchrony and psychopathology, Mendle [1] speculated that asynchronous youth might experience heightened confusion and uncertainty because each body part grows unpredictably at its own pace.…”
Section: Pubertal Asynchrony: a Protective Factor For Boys But A Risk Factor For Girlssupporting
confidence: 86%
See 2 more Smart Citations
“…Pubertal asynchrony puts girls at risk of peer victimization above and beyond pubertal status and other covariates. The finding is consistent with prior work showing the positive link between pubertal asynchrony and maladjustment, such as depression, in girls (Stumper et al, 2020;Thompson et al, 2016). In explaining the association between pubertal asynchrony and psychopathology, Mendle [1] speculated that asynchronous youth might experience heightened confusion and uncertainty because each body part grows unpredictably at its own pace.…”
Section: Pubertal Asynchrony: a Protective Factor For Boys But A Risk Factor For Girlssupporting
confidence: 86%
“…There are only two studies that we are aware of that empirically tested the effect of pubertal asynchrony on psychosocial adjustment, both of which focused on depressive symptoms. Thompson and colleagues [18] identified three groups of pubertal asynchrony patterns in a study of 13-year old girls: girls whose breast and pubic hair growth were synchronous (i.e., synchrony group), girls whose Tanner stage rating for pubic hair was greater than their Tanner stage rating for breast development (i.e., pubarche group), and girls whose Tanner stage rating for breast development was greater than their Tanner stage rating for pubic hair growth (i.e., thelarche group). The results showed that the synchronous group had fewer depressive symptoms at age 20 than the thelarche or pubarche groups, but no such association was found at age 15.…”
Section: Pubertal Asynchrony and Peer Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research in pubertal synchrony has been limited, there has been some consideration of the correspondence between adrenal and gonadal indicators of development (Corley, Beltz, Wadsworth, & Berenbaum, ; Susman et al., ). Most notably, Thompson, Hammen, and Brennan () reported that asynchronous pubertal development in girls was associated more strongly with depression in late adolescence. Synchrony will be an important avenue for future work, especially because researchers often collapse across different puberty indicators, and the optimal statistical approaches for comparing and contrasting across indicators are still unclear.…”
Section: How To Capture Individual Differences In Pubertal Developmenmentioning
confidence: 99%
“…Puberty is the transitional stage between childhood and adulthood. It is one of the most critical developmental stages and is characterized by sexual maturation, both physiologically and psychologically [1]. Pubertal timing refers to individual differences in the timing of pubertal development [2].…”
Section: Introductionmentioning
confidence: 99%